Caring Under Pressure: Investigating Parental Attitudes in Mother-Child Chronic Illness Dynamics - Melda Celik; Esma Altinel Acoglu; Beril Aydin; Emel Isiyel; Siddika Songul Yalcin (MDPI AG, 2024)
Background: The presence of chronic illnesses in both a mother and a child poses a significant challenge for mothers in managing these conditions, yet how maternal attitudes adapt to dual illness remains poorly understood. This study aims to explore parenting styles in families dealing with mother-child chronic illnesses. Methods: Mothers of children aged 2-6 were recruited from three pediatric clinics and categorized based on the health status of both the mother and the child. Data collection included case files and the Parental Attitude Scale (PAS), which assessed democratic, authoritarian, overprotective, and permissive attitudes. The interaction between mother-child health status and higher levels of parental subscales was analyzed using the chi-square test. Multiple logistic regression analysis was then performed to evaluate this interaction, controlling for confounding baseline characteristics. Results: In total, 878 mother-child pairs were included. Mothers exhibited varying attitudes based on education, employment, and the child's age. Chronic illness in both mother and child and only the child having an illness were significantly associated with higher overprotective scores (p < 0.001). The percentage of mothers with high permissive scores was higher when only the mother had an illness and when both were healthy, compared to the case of both mother and child having an illness (p = 0.018). After adjusting for confounding factors, having a sick child showed a 1.6-fold increase in the likelihood of a high overprotective score, and both the mother and child having an illness showed a 2.94-fold increase. Similarly, after adjusting for the same confounding factors, the likelihood of a high permissive score was 2.56 times lower when both were ill compared to when both were healthy. Conclusions: This study reveals that when a child is affected by a chronic illness-whether or not the mother is also ill-mothers tend to exhibit higher levels of overprotection and lower levels of permissiveness, while their levels of authoritarianism and democratic attitudes in parenting remain relatively stable.